If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + -54 = 2(7p + 3) Reorder the terms: -54 + 4p = 2(7p + 3) Reorder the terms: -54 + 4p = 2(3 + 7p) -54 + 4p = (3 * 2 + 7p * 2) -54 + 4p = (6 + 14p) Solving -54 + 4p = 6 + 14p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14p' to each side of the equation. -54 + 4p + -14p = 6 + 14p + -14p Combine like terms: 4p + -14p = -10p -54 + -10p = 6 + 14p + -14p Combine like terms: 14p + -14p = 0 -54 + -10p = 6 + 0 -54 + -10p = 6 Add '54' to each side of the equation. -54 + 54 + -10p = 6 + 54 Combine like terms: -54 + 54 = 0 0 + -10p = 6 + 54 -10p = 6 + 54 Combine like terms: 6 + 54 = 60 -10p = 60 Divide each side by '-10'. p = -6 Simplifying p = -6
| 2v=2-4/3 | | 9x+-14=2x | | 6x+-1+6x=11 | | 50(t-1)=1.8 | | 2*x^2-8=0 | | 18x-10=0 | | 8x+7=2x+13 | | -117=5x-2(-1-6x) | | 2/n=n/15 | | 7-8x+9x-2=5x+2-x | | 9/N=1/4 | | -7(1-4)=13(2y-3) | | x(-6x+5x+x^2)=0 | | n+n-1=11 | | 14(6-2x)=x | | 7a+a=80 | | 8(3-2x)=x | | 8(4-2x)=x | | 9(3-2x)=x | | 9(4-2x)=x | | 6x-30=x+5 | | 3x+35=4x+35 | | (5x-4)/3-5(7+6x)/8=7 | | 32-4x=2x | | 32-4x=7x | | 32-4x=6x | | 2X+5=13+4X | | a/8=13 | | 32-4x=6x+22 | | n-11=25 | | 2w+8x-11y+7w+4x+4y= | | 9x+6=3x-12 |